Integration of GIS and AHP techniques for the sustainability of groundwater potential zones in the coastal environs - Moses, Ratheesh; Sathiyamoorthy, Mahenthiran (Frontiers in Water, 2025)
Coastal aquifers are facing significant threats from overexploitation, seawater intrusion, and reduced recharge. Effective groundwater management necessitates a precise spatial evaluation of groundwater potential. This research aims to identify Groundwater Potential Zones (GWPZ) of Tarangambadi Taluk in Mayiladuthurai district, Tamil Nadu, using integrated GIS, Remote sensing, and the Analytical Hierarchy Process (AHP) methods. The study included fourteen thematic layers selected based on hydrogeological relevance. Each layer's weight was calculated utilizing the AHP methods, facilitated through analysis of weighted overlay in GIS to produce the spatial distribution of the GWPZ. The study zone was classified into five potential categories. Analysis indicates that 52% of the area is classified within high to very high potential zones, predominantly located in the central and western taluk, characterized by favorable geological conditions. Conversely, approximately 19% of the area, primarily along the eastern coastline, is categorized as low to very-low potential zones due to factors such as impervious surfaces and saline intrusion risks. The resulting GWPZ map aligns well with borewell data, affirming its precision and utility. The outcomes serve as a valuable resource for sustainable planning and aquifer management in coastal areas.